PERAN GURU PADA PROGRAM GREEN SCHOOL UNTUK MENGUATKAN KARAKTER PEDULI LINGKUNGAN PADA PESERTA DIDIK DI SEKOLAH ADIWIYATA NASIONAL SD YPWKS V - Sari, Nadila Hepta; Andriana, Encep; Hendracipta, Nana (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aims of this study were to determine the design of the green school program, the implementation of the green school program, teachers' understanding of the green school program, and the role of teachers in the green school program in strengthening the character of caring for the environment at SD YPWKS V. This study apllied qualitative descriptive. The subjects of this study were the principal, class teachers, and students at SD YPWKS V. Data collection techniques used were interviews, observations, and documentation. Data obtained qualitatively showed that the role of teachers in designing the program was to identify environmental problems at schools and determine specific needs must be addressed through the green school program, actively participate in formulating ideas and concepts and designing the curriculum. In the implementation of the green school program, most residents at SD YPWKS V have implemented the green school program during teaching and learning activities and activities outside the classroom and have applied it in everyday life. In addition, teachers at SD YPWKS V already understand the concept of green school so that teachers can understand the indicators of students who already have environmental awareness. The role of teachers in the formation of environmentally awareness characters is that teachers become facilitators for students to provide understanding to students, direct and guide them, and provide concrete examples so that students at YPWKS Elementary School already have environmentally awareness characters.